Global Change and the Soil Microbiome: A Human-Health Perspective - Ochoa-Hueso, Raúl (Frontiers in Ecology and Evolution, 2017)
The importance of the gut and the soil microbiomes as determinants of human and ecosystem health, respectively, is gaining rapid acceptation in the medical and ecological literatures. This suggests that there is a wealth of highly transferable knowledge about the microbial ecology of human and non-human ecosystems that is currently being generated in parallel, but mostly in isolation from one another. I suggest that effectively sharing this knowledge could greatly help at more efficiently understanding and restoring human health and the functioning of ecosystems, which are currently under wide-spread pressure. I illustrate this by comparing the effects of nitrogen deposition on ecosystem carbon sequestration with unhealthy dietary habits and human disease. The deposition of N, a key nutrient for plant growth, may increase carbon sequestration (equivalent to obesity) through several mechanisms, including a reduction in the ability of soil microbes to process organic matter, which some argue could help mitigate climate change. However, this usually results in a degradation of ecosystem health and, thus, cannot represent a real solution. Similarly, human obesity is linked to an alteration of the composition and functioning of microbial communities inhabiting the gut, which is often attributed to unhealthy dietary habits, including ingesting high amounts of simple sugars and processed foods. Finally, I advocate for the explicit recognition of the many commonalities between the functioning of the gut and ecosystems and a broader multidisciplinary collaboration among experts in ecology and human health, including the engineering of soil microbial communities designed ad-hoc to restore ecosystem health.